INFLUENCE OF CONTACT TIME ON LOADING 99MO(N,Î³) WITH ALUMINA COLUMN IN 99MO / 99MTC GENERATOR - Sulaiman, Sulaiman; Sugiharto, Yono; Setiawan, Gatot; Chairuman, Chairuman; H.G., Adang (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Alumina is usually used for 99Mo absorbers obtained from 235U fission product because the use of 235U is getting limited, and as an alternative 99Mo obtained from natural MoO3 irradiation was used. The problem is that 99Mo produced was not carrier-free as 99Mo from 235U fission product because not all MoO3 is activated to 99Mo, then it is necessary to know the effect of contact time when loading 99Mo into the alumina column. To find out the effect of contact time, the experiment was carried out using 99Mo pH 4, acid alumina column, contact time was varied between 1 to 60 minutes with interval of 15 minutes, and the column was eluted using 2 kinds of eluent namely 0.9% NaCl and MEK. The elution of 99Mo/99mTc generator is performed 3 times, days 1, 2 and 3. The results showed that the performance of alumina in absorbing 99Mo influenced by time. The optimal contact time is 15 minutes for 0.9% NaCl solution and 45 minutes for MEK. The amount of 99Mo breakthrough (µCi99Mo/mCi99mTc) from the alumina column increases with elution time both using 0.9% NaCl or MEK. The 99mTc eluate obtained from this study does not meet standard requirements. The use of a tandem column is needed to prevent 99Mo breakthrough on the 99Mo/99mTc generator to get the 99mTc which meet standard requirement.